2011
DOI: 10.1007/s11230-011-9311-1
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic assessment of the colonisation patterns in Spauligodon atlanticus Astasio-Arbiza et al., 1987 (Nematoda: Oxyurida: Pharyngodonidae), a parasite of lizards of the genus Gallotia Boulenger: no simple answers

Abstract: Parasite taxonomy traditionally relies on morphometric and life-cycle characteristics which may not reflect complex phylogenetic relationships. However, genetic analyses can reveal cryptic species within morphologically described parasite taxa. We analysed the phylogenetic variation within the nematode Spauligodon atlanticus Astasio-Arbiza, Zapatero-Ramos, Ojeda-Rosas & Solera-Puertas, 1987, a parasite of the Canarian lizard genus Gallotia Boulenger, inferring the origin of their current association. We also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…Six hundred microlitres of lysis buffer (0.5 M Tris, 0.1 M EDTA, 2% sodium dodecyl sulphate (SDS), pH 8.0) and 5 -20 ml of proteinase K (25 mg/ml) were added to small pieces of tissue and incubated at 568C overnight. These primers have been used previously to amplify DNA of other nematodes infecting reptiles (Hasegawa et al, 2009;Jorge et al, 2011). The supernatant was transferred to new Eppendorf tubes with 600 ml of ice-cold isopropanol, frozen from 3 h to overnight, and centrifuged for 15 -30 min at 14,000 rpm at 2 48C.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Six hundred microlitres of lysis buffer (0.5 M Tris, 0.1 M EDTA, 2% sodium dodecyl sulphate (SDS), pH 8.0) and 5 -20 ml of proteinase K (25 mg/ml) were added to small pieces of tissue and incubated at 568C overnight. These primers have been used previously to amplify DNA of other nematodes infecting reptiles (Hasegawa et al, 2009;Jorge et al, 2011). The supernatant was transferred to new Eppendorf tubes with 600 ml of ice-cold isopropanol, frozen from 3 h to overnight, and centrifuged for 15 -30 min at 14,000 rpm at 2 48C.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Recently, several studies reported the discovery of cryptic species within what were considered single species, through the use of population genetics, phylogeographic or phylogenetic tools (Jorge et al. ; Nadler and Pérez‐Ponce de León ; Poulin ; Oliveira et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…One recent case of possible cryptic species in parasites has been observed in the nematode genus Spauligodon , infecting endemic lizards of the genus Gallotia in the Canarian archipelago (Jorge et al. ). Spauligodon atlanticus Astasio‐Arbiza et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations